The alcohol dependence syndrome: A legacy of continuing clinical and scientific importance - Stockwell, Tim (Blackwell Publishing Ltd, 2015)
This paper offers some reflections on Griffith Edwards' continuing legacy with particular reference to his and Milton Gross's formulation of alcohol dependence as a 'provisional' clinical syndrome. The ideas and language from this seminal paper have heavily influenced international diagnostic classification systems. However, it is observed that there has also been significant (and increasing) divergence-in particular around the original proposal that dependence and negative alcohol-related consequences are independent, if inevitably inter-related dimensions. This is most apparent in the conflation of alcohol-related problems and dependence phenomena implicit in DSM-V. It is also argued that the alcohol dependence syndrome (ADS) has substantial continuing influence and relevance to current clinical practice. The hypothesis that degree of alcohol dependence is a useful indicator of the possibility of a return to controlled drinking continues to receive support, and underpins the widespread implementation of brief interventions for 'early stage' problem drinkers. It is suggested that the kind of careful clinical observations that underpinned the original concept of alcohol dependence have continuing relevance to the formulation of improved understanding, measurement instruments, diagnostic systems and clinical responses.